Performance Assessment Creative Thinking Rubric in Science Technology Engineering and Mathematics (STEM) Learning - Windyariani, Sistiana; Setiono, Setiono (Universitas Negeri Semarang, 2024)
This research has the objective to develop an alternative rubric for evaluating creative thinking performance in STEM (Science, Technology, Engineering, and Mathematics) education. The research employs a Design-Based Research (DBR) methodology, which involves four stages: 1) Designing a prototype for performance assessment (design), 2) Conducting trials to test the developed assessment (test), 3) Performing evaluations, and 4) Reflecting on and addressing any deficiencies in the developed tasks and rubrics. The research involved respondents completing performance assessment tasks using the newly developed criteria/ rubric. The participants included 57 students from the Biology Education research Program at Universitas Muhammadiyah Sukabumi, enrolled in the 3rd and 5th semesters. This research resulted in a valid and practical assessment of creative thinking performance in STEM learning, with the Performance Assessment Rubric achieving an average percentage of 83.5% (proper). The research produced a creative thinking performance assessment instrument that can be used as an evaluation tool in STEM education. Further implications suggest incorporating these assessments into STEM curricula and training educators to use them effectively.